Semiconducting mineral induced photochemical conversion of PAHs in aquatic environment: Mechanism study and fate prediction - Cai, Zhengqing; Fuquan Yang; Yanyu Song; Yongdi Liu; Liu, Wen; Qilin Wang; Xianbo Sun (Science of The Total Environment, 2023)
Semiconducting minerals (such as iron sulfides) are highly abundant in surface water, but their influences on the natural photochemical process of contaminants are still unknown. By simulating the natural water environment under solar irradiation, this work comprehensively investigated the photochemical processes of anthracene (a typical Polycyclic Aromatic Hydrocarbons) in both freshwater and seawater. The results show that the natural pyrite (NP) significantly promotes the degradation of anthracene under solar illumination via 1) NP induced photocatalytic degradation of anthracene, and 2) Fenton reaction due to the NP induced photocatalytic generation of H2O2. The material characterization and theoretical calculation reveal that the natural impurity in NP enlarges its band gap, which limits the utilization of solar spectra to shorter wavelength. The contribution of generated reactive intermediates on anthracene degradation follows the order of 1O2 > OH > O2− in freshwater and O2− > 1O2 > OH in seawater. The photochemically generated H2O2 is a vital source for OH generation (from Fenton reaction). The steady-state concentration of OH, 1O2 and O2− in freshwater were monitored as 3.0 × 10−15 M, 1.1 × 10−13 M, and 4.5 × 10−14 M, respectively. However, the OH concentration in seawater can be negligible due to the quenching effects by halides, and the 1O2 and O2− concentrations are higher than that in freshwater. An anthracene degradation kinetic model was built based on the experimentally determined reactive intermediates concentration and its second order rate constant with anthracene. Moreover, the anthracene degradation pathway was proposed based on intermediates analysis and DFT calculation, and its toxicity evolution during the photochemical process was assessed by quantitative structure-activity relationship (QSAR) based prediction. This finding suggests that the natural semiconducting minerals can affect the fate and environmental risks of contaminants in natural water.
Keywords: Fenton; Natural semiconductors; Natural weathering; pahs; Photocatalytic